2018
DOI: 10.15407/microbiolj80.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Some Essential Oils on Candida Genus Clinical Isolates

Abstract: The purpose of the work was to study the qualitative composition of the concomitant opportunistic pathogenic microbiota in the patients suffering from pulmonary tuberculosis; analyze the sensitivity of the isolates to essential oils and antibiotics. Methods. For antibiotic susceptibility and antimicrobial activity testing was used disc diffusion method. The analysis of essential oils was carried out by Gas Chromatography method. Results. The study showed that microscopic Candida genus fungi were the dominating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
2
0
2
Order By: Relevance
“…Marino et al (1999) determined the high antibacterial effect of essential oils of Thymus vulgaris L. against common bacteria (Pseudomonas aeruginosa, Klebsiella pneumoniae, Enterococcus faecalis, Salmonella typhimurium, Escherichia coli and Staphylococcus aureus). Our previous studies showed high antimycotic activity of essential oils against Candida genus microscopic fungi (Kryvtsova et al, 2017(Kryvtsova et al, , 2018Salamon et al, 2017). The antimicrobial effect of essential oils against oral cavity pathogens was shown in (Koba et al, 2011).…”
Section: Discussionmentioning
confidence: 94%
“…Marino et al (1999) determined the high antibacterial effect of essential oils of Thymus vulgaris L. against common bacteria (Pseudomonas aeruginosa, Klebsiella pneumoniae, Enterococcus faecalis, Salmonella typhimurium, Escherichia coli and Staphylococcus aureus). Our previous studies showed high antimycotic activity of essential oils against Candida genus microscopic fungi (Kryvtsova et al, 2017(Kryvtsova et al, , 2018Salamon et al, 2017). The antimicrobial effect of essential oils against oral cavity pathogens was shown in (Koba et al, 2011).…”
Section: Discussionmentioning
confidence: 94%
“…The selected literature data on anthocyanins raised the hope for their wide-spread use for the prevention and therapy of many diseases [14]. In our preceding works, we showed the antimicrobial activity of materials obtained from vegetable matter, phytoextracts and essential oils that showed the antimicrobial activity against isolates from the oral cavity, pharynx, and respiratory tract, including antibiotic-resistant ones [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Одним з перспективних, на нашу думку, альтернативних методів лікування кандидозів, є використання біологічно активних речовин природного походження. Зокрема, позитивні результати у лікуванні резистентних до анти-біотиків кандидозів слизистих ротової порожнини показали ефірні олії (Kryvtsova et al 2018). Окрім ефірних олій, позитивний результат було отримано і в досліді дії фітопрепаратів на пародонтит, викликаний різними інфекційними агентами, в тому числі й асоціаціями кандиди з умовно патогенними бактеріями (Kryvtsova 2019;Kryvtsova, Kostenko 2019;Kryvtsova, Kostenko 2020).…”
Section: вступunclassified